Cellular populations and thermosensing mechanisms of the hypothalamic thermoregulatory center - Siemens, Jan; Kamm, Gretel B. (Pflügers Archiv, 2018)
Temperature affects all aspects of life down to the diffusion rates of biologically active molecules and reaction rates of enzymes. The reciprocal argument holds true as well and every biological process down to enzymatic reactions influences temperature. In order to assure biological stability, mammalian organisms possess the remarkable ability to maintain internal body temperature within a narrow range, which in humans and mice is close to 37 °C, despite wide environmental temperature variations and different rates of internal heat production. Nevertheless, body temperature is not a static property but adaptively regulated upon physiological demands and in the context of pathological conditions. The brain region that has been primarily associated with internal temperature regulation is the preoptic area and the anterior portion of the hypothalamus. Similar to a thermostat, this brain area detects deep brain temperature, integrates temperature information from peripheral body sensors, and-based on these inputs--controls body temperature homeostasis. Discovered more than a century ago, we still know comparatively little about the molecular and cellular make-up of the hypothalamic thermoregulatory center. After a brief historic outline that led to the discovery of the thermoregulatory center, we here review recent studies that have considerably advanced our understanding of hypothalamic thermoregulation. We touch upon proposed mechanisms of intrinsic deep brain temperature detection and focus on newly identified hypothalamic cell populations that mediate thermoregulatory responses and that provide novel entry points not only to shed light on the mechanistic underpinnings of the thermoregulatory center but also to probe its therapeutic value.
Gesehen am 04.10.2019